2014
DOI: 10.1007/s11274-014-1764-3
|View full text |Cite
|
Sign up to set email alerts
|

Highly effective bacterial agents against Cimbex quadrimaculatus (Hymenoptera: Cimbicidae): isolation of bacteria and their insecticidal activities

Abstract: Cimbex quadrimaculatus (Hymenoptera: Cimbicidae) is one of the serious pests of almonds in Turkey and worldwide. Since there is no effective control application against this pest, it has been a serious problem up to now. Therefore, we aimed to find an effective bacterium that can be utilized as a biocontrol agent against C. quadrimaculatus in pest management. We isolated seven bacteria from dead and live C. quadrimaculatus larvae, and evaluated the larvicidal potency of all isolates on the respective pest. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…However, its antimicrobial/probiotic properties seem unexplored and most reports refer to clinical specimens [ 46 ] with the exception of one study where K . gibsonii is proposed for agricultural use as a microbial pesticide [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, its antimicrobial/probiotic properties seem unexplored and most reports refer to clinical specimens [ 46 ] with the exception of one study where K . gibsonii is proposed for agricultural use as a microbial pesticide [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus spp. are commonly isolated from various insect groups including whiteflies (Davidson et al, 2000;Yu et al, 2008;Ateyyat et al, 2010;Cakici et al, 2015;Pu & Hou, 2016). Ateyyat et al (2009) tested Staphylococcus gallinarum isolated from B. tabaci against the second instar nymphs of the pest through the leaf dipping method and reported that bacteria generated 19.5 and 28% infection after 3 and 5 d, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Plates were incubated for 2-3 days at 30°C. Pure cultures were obtained from bacterial colonies growing at the end of incubation according to their size, color and morphology (Ozkan-Cakici et al, 2015).…”
Section: Isolation and Purification Of The Bacteriamentioning
confidence: 99%